Śahīda Saṃnyāsī, arthāt, Āryya vīra Svāmī Śraddhānanda jī kā Hindu jāti ke liye ātma-samarpaṇa - Zebā, Kiśanacanda (SAMP early 20th-century Indian books project ;, 1927)
On the life of Swami Sraddhananda, leader of Arya-samāj.